TINJAUAN TINGKAT KESEHATAN BANK SEBELUM DAN SESUDAH MERGER PADA PT BANK TABUNGAN PENSIUNAN NASIONAL TBK - Kharisma Sekar Ramadhanti Enshito (2021)
Banks must have a good strategy in order to keep up with the current banking competition. One strategy that can be done is to expand, both internally and externally. One of the strategies undertaken is to conduct mergers and acquisitions. The purpose of this final project is to determine the soundness of Bank BTPN before and after the merger through financial statement analysis. The method used is the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital). From the results of the study conducted, there was a decrease in several bank soundness ratios. This happened due to several impacts of the merger which resulted in a decrease in the ratio, including the challenges of macroeconomic conditions that were under pressure as well as an increase in company expenses and was affected by the COVID-19 pandemic.